Coherence-Resonance-Induced Neuronal Firing near a Saddle-Node and Homoclinic Bifurcation Corresponding to Type-I Excitability - Jia, Bing (冰贾); Gu, Hua-Guang (华光 古); Li, Yu-Ye (玉叶 李) (Chinese physics letters, 2011)
Excitability is an essential characteristic of excitable media such as nervous and cardiac systems. Different types of neuronal excitability are related to different bifurcation structures. We simulate the coherence resonance effect near a saddle-node and homoclinic bifurcation corresponding to type-I excitability in a theoretical neuron model, and recognize the obvious features of the corresponding firing pattern. Similar firing patterns are discovered in rat hippocampal CA1 pyramidal neurons. The results are not only helpful for understanding the dynamics of the saddle-node bifurcation and type-I excitability in a realistic nervous system, but also provide a practical indicator to identify types of excitability and bifurcation.